Bakti Sosial Penanaman 700 Bibit Pohon Buah Pada Desa Lumban Bul-Bul Kecamatan Balige Kabupaten Toba - Damanik, Evo Marisi Tumpal; Simarmata, Bangettua; Sitanggang, Mery Suliyanti H.; Girsang, Tonggo Sangap Timbul (Jurnal Dehasen Untuk Negeri, 2025)
Balige District is one of the hometowns of one of the students of the Bina Prestasi Independent Polytechnic. The selection of this location was agreed to be the place for Community Service because it is to realize the "Go Green For Better Nature We Keep, We Care, We Preserve" movement. Balige District is also known as SMA Negeri 1 Laguboti, which is located near Balige Lumban Bul-bul Beach. Head of the Business Administration Study Program, Mr. Evo M. T. Damanik, S.E., M.M. Together with the lecturers by mobilizing the Business Administration Study Program Student Association with the Chairman of the Committee Afitz Abdala Hasibuan, Dini Secretary Cristiani Sibagarian, the Treasurer of Bunga Lestari Ginting realizes Community Service of 700 fruit tree seedlings well starting from May 9-11, 2025. The team that departed was 3 supervisors and 49 members of the Student Association Committee of the Business Administration Study Program – Polytechnic Mandiri Bina Prestasi – Medan. At the location, they were welcomed by the Head of the Balige Police Department of Toba Regency Mr. Harianto Butar-Butar S.E., M.Si, the Head of the Toba Regency Environmental Agency Mrs. Melva Panjaitan, the Balige Sub-district Head of Toba Regency Mr. Mangapul, the Head of Lumban Bul-Bul Village, Mrs. Melva Panjaitan, the parents of the students Mr. Ahmad Ridho Pelupessy Sianipar and Mrs. Frelly Novinta Pangaribuan, representatives of indigenous community leaders Mr. Paber Simangunsong and local communities. This Community Service is in accordance with the work calendar of the Business Administration Study Program and is planned to be carried out again every year with the choice of the region of origin of students who are active to provide organizational spirit for students.